2009
DOI: 10.1051/0004-6361/200911752
|View full text |Cite
|
Sign up to set email alerts
|

Composition of KBO (50000) Quaoar

Abstract: Aims. The objective of this work is to investigate the physical properties of objects beyond Neptune -the new frontiers of the Solar System -and in particular to study the surface composition of (50 000) Quaoar, a classical Transneptunian (or Kuiper Belt) object. Because of its distance from the Sun, Quaoar is expected to have preserved, to a degree, its original composition. Our goals are to determine to what degree this is true and to shed light on the chemical evolution of this icy body. Methods. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 36 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…The spectra are compared with a previously obtained spectrum (Q2008 in Fig. 1) also acquired at the VLT-ESO facility, but with different instruments (FORS for the visible, ISAAC for the J-band, and SINFONI for the H-and K-bands) whose spectra were adjusted by means of photometric colours (Dalle Ore et al 2009). The advantage of the X-Shooter spectrograph is in the simultaneous spectrum acquisition from the visible to the NIR, resulting in the more accurate spectral information needed to investigate surface composition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The spectra are compared with a previously obtained spectrum (Q2008 in Fig. 1) also acquired at the VLT-ESO facility, but with different instruments (FORS for the visible, ISAAC for the J-band, and SINFONI for the H-and K-bands) whose spectra were adjusted by means of photometric colours (Dalle Ore et al 2009). The advantage of the X-Shooter spectrograph is in the simultaneous spectrum acquisition from the visible to the NIR, resulting in the more accurate spectral information needed to investigate surface composition.…”
Section: Discussionmentioning
confidence: 99%
“…Both are indicative of a young surface possibly refreshed by cryo-volcanic activity. The accurate fitting model by Dalle Ore et al (2009) on high quality data reported a surface composition containing crystalline water ice, CH 4 , as well as possibly C 2 H 6 and organic materials, products of irradiation of CH 4 . The band at 2.2 μm was present in the observations of Dalle Ore et al (2009) and was fitted by their model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, tholins are an effective coloring agent in models of solid surfaces (e.g., Hoffman et al 1993;Dalle Ore et al 2009;Owen et al 2001;and Cruikshank et al 2005).…”
Section: Introductionmentioning
confidence: 99%